Geotrack: an end-to-end framework to support moving objects - Silva, Alison Hedigliranes da (2024)
The proliferation of intensive use of geolocation devices has led to considerable battery drain in these devices, typically stemming from excessive HTTP calls or extreme precision in device location, resulting in difficulties for applications requiring frequent location updates. Faced with this issue, this study presents a framework developed to collect, process, and visualize geolocation data on mobile devices, particularly smartphones, aiming to promote greater battery efficiency. The solution aims to optimize the development process of geolocation-focused applications through a Java framework, reduce battery consumption by automating HTTP call managementa and enhance geolocation data precision with an Android library, and provide data visualization capabilities with a JavaScript library.